AKTIVITAS ANTIBAKTERI DAN UJI FORMULASI KRIM EKSTRAK ETANOL DAUN KERSEN TERHADAP PROPIONIBACTERIUM ACNES - Maulana Tegar AdityaNugraha (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2022)
Acne is a skin disease that is very common in adolescence to adulthood. The main bacteria that causes acne is Propionibacterium acnes ATCC 6919 P. acnes plays a role in the pathogenesis of acne by producing lipases which break down free fatty acids from skin lipids. This indicates that ethanol extract of cherry leaves at a minimum concentration of 2.5% has antibacterial activity against propionibacterium acnes. . This study aims to determine the physical properties and activity of ethanol extract cream of cherry leaves against Propionibacterium acne. This type of research is experimental research using the well diffusion method and the diameter of the inhibition zone. In this study, the physical properties (organoleptic, spreadability, adhesion, pH, protection) and antibacterial activity will be tested. The cream concentrations of ethanol extract of cherry leaves used in this study were 5% and 10%. The analysis used is descriptive analysis. Physical properties test results. Cream of cherry leaf ethanol extract at concentrations of 5% and 10% has a physical appearance, pH value, dispersibility, good protection and poor adhesion to formla 1 and formula 2 has good adhesion. Antibacterial activity The ethanol extract cream of cherry leaves at a concentration of 5% and 10% showed antibacterial activity against Propionibacterium acnes.